Catadores de materiais recicláveis : a luta para tirar o direito do papel - Camila Mattarelli de Abreu e Silva (2020)
Works of organizations related to the catholic church directed to homeless people started the organizational process of waste pickers in associations and cooperatives in Brazil. In this process, while discussing issues about citizenship, the right to have rights, these workers realized the value and importance of their labor, which, in addition to providing their family’s livelihood, brings environmental, social, and economic benefits to the collectivity, by separating recyclable materials and putting them back into the productive cycle. The construction of their self-perception as citizens and workers allowed the construction of the perception that it is unfair the fact that they are not recognized for their work by the society and the government, including not being remunerated for it. Thereafter, it has been constructed the idea that waste pickers have the right to be hired to do the municipal waste selective collection services. In order to analyse the struggling process of the waste pickers for their organizations to be hired, case studies were developed in four municipalities with the purpose of comprehend how the different dimensions of the Interpretive Frame of Collective Action mobilized on the bases, including perceptions of political opportunities, relate to the choices concerning to the repertory of collective action used. The analysis had support on SMT, mainly of relevant concepts on PPT, as repertory of collective action, political opportunities and framing. The contribution of studies of legal mobilization were important too. With this study, it was possible to understand a tendency of the waste pickers leaderships to avoid confrontational strategies, privileging forms of interaction called by Abers, Serafim, and Tatagiba of: policy of proximity and institutional participation; whenever possible. If the public management is read as impermeable to the demands of the waste pickers, the leaderships adopt other possibilities: the implementation of space of interlocution in the ambit of civil society, the FMLC, and the forwarding of demands to justice system institutions, such as the Ministério Público and the Defensoria Pública. Collective actions with confrontational disposition are less common, in general, they occur when there is the perception of some threat consider highly relevant by the leaderships. Although it is possible to note a strong influence of the leaderships’ perceptions upon opportunities and political threats on the decision-makings related to the repertory, it is important to highlight that the capacity of the waste pickers agency is also perceptible, given the formation of wide nets of support and the success on the approval of legislation - 12.305/2010 - which nowadays is presented as a juridical opportunity to the waste pickers organizations in Brazil. Therefore, it is possible to realize that waste pickers not only take advantage, but they create political opportunities as well.